Effect of Red Ginger Addition and Drying Temperature Variations on Quality Characteristics and Antioxidant of Cat’s Whiskers Leaf Teabags - Rizki Putri Sari Manik; Ismed Suhaidi; Sentosa Ginting (Indonesian Journal of Agricultural Research, 2023)
Tea is a type of beverage that is widely consumed in various countries due to its high antioxidant content and its beneficial for health. This study was conducted to determine the effect of the addition of red ginger and variations in drying temperature on the quality characteristics and antioxidant content of cat whisker leaf tea bags. The study used a factorial Completely Randomized Design (CRD) method consisting of two factors, the addition of red ginger (10%, 20%, 30%, and 40%) and variations in drying temperature (40oC, 50oC, and 60oC). The results show that the addition of red ginger had a highly significant effect on water content, ash content, water-soluble ash content, crude fiber content, pH, antioxidant content, aroma hedonic value, taste hedonic value, and general acceptance hedonic value. Variations in drying temperature had a highly significant effect on water content, ash content, water-soluble ash content, fiber content, and antioxidant content. This variation of drying temperature also had no significant effect on pH, hedonic aroma value, taste hedonic value, color hedonic value, and general acceptance hedonic value. The best results showed that the addition of ginger at 40% and a drying temperature of 60oC resulted in the best quality of tea bags.